Stress Cardiovascular Magnetic Resonance Imaging for the Detection of Coronary Artery Disease - Giulia Vinco; Clementina Dugo; Marzia Rigolli; Cristina Demattè; Cristiana Giovanelli; Fabio Caruso; Alessandro Marinetti; Andrea Chiampan; Carmelo Cicciò; Carlo Cosimo Quattrocchi; Giulio Molon; Maurizio Del Greco (Reviews in Cardiovascular Medicine, 2023)
Stress cardiovascular magnetic resonance (CMR) imaging has received extensive validation for the assessment of ischemic heart disease. Without ionizing radiation exposure, it offers in-depth information regarding cardiac structure and function, presence and degree of myocardial ischemia and myocardial viability. When compared to other imaging modalities, it has demonstrated excellent sensitivity and specificity in detecting functionally relevant coronary artery stenosis, as well as strong prognostic value in clinical risk stratification. The current scientific data support a greater expansion of stress CMR. This review investigates the current stress CMR techniques and protocols, as well as its relevance in diagnosis and prognosis of coronary artery disease.